Ultrahigh Density of Atomic CoFe-Electron Synergy in Noncontinuous Carbon Matrix for Highly Efficient Magnetic Wave Adsorption - Huang, Wenhuan; Qiu, Qiang; Yang, Xiufang; Zuo, Shouwei; Bai, Jianan; Zhang, Huabin; Pei, Ke; Che, Renchao (Nano-micro letters, 2022)
Highlights A typical 3D porous carbon sponge of CoFe@PCS exhibited the continuous distribution of nano-meso-micro-hierarchical pores in the range of 1 nm–15 μm. The ultrahigh-density distribution of the nanoscale polarized charges (+ / −) along the edges of the pores resulted in nanoscale variable capacitors. The high density of Co–Fe electromagnetic coupling on the carbon matrix, showing the enhanced electromagnetic wave attenuation. Improving the atom utilization of metals and clarifying the M–M’ interaction is both greatly significant in assembling high-performance ultra-light electromagnetic wave-absorbing materials. Herein, a high-temperature explosion strategy has been successfully applied to assemble the hierarchical porous carbon sponge with Co–Fe decoration via the pyrolysis of the energetic metal organic framework. The as-constructed hybrid displays a superior reflection loss (RL) value of − 57.7 dB and a specific RL value of − 192 dB mg −1 mm −1 at 12.08 GHz with a layer thickness of 2.0 mm (loading of 15 wt%). The off-axis electron hologram characterizes the highly distributed numerous polarized nanodomain variable capacitors, demonstrating the dipole and interfacial polarization along the edges of the nanopores. More importantly, the X-ray absorption spectroscopy analysis verifies the mutual interaction between the metal cluster and carbon matrix and the electronic coupling responsible for the greatly improved electromagnetic wave absorption.